2009
DOI: 10.1159/000255970
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Hyperintensities Predict Functional Stroke Outcome

Abstract: Background: Growing evidence suggests that white matter hyperintensities (WMHs) are implicated in stroke recurrence and mortality, and their location can be a critical factor. This study evaluated the impact of periventricular WMHs (PVWMHs) and subcortical WMHs (SWMHs) on poststroke functional outcomes. Methods: Brain MRI was performed on 187 acute ischemic stroke patients (57.8% male; mean age = 64.3 years) recruited from the Kaohsiung Municipal Hsiao-Kang Hospital from February 2007 to January 2008. A Fazeka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 67 publications
5
42
0
Order By: Relevance
“…This finding is consistent with prior observations in other conditions; the extent of PLA when compared with SLA more strongly correlates with cognitive decline in the nondemented elderly population, [14][15][16] progression from mild cognitive impairment to Alzheimer disease, 17 burden of aortic atherosclerosis, 18 poor functional outcome after stroke, 11 and risk of recurrent hemorrhage in patients with lobar intracerebral hemorrhage. 19 It has been suggested that SLA predominantly disrupts the short association fibers that connect adjacent gyri to each other, whereas PLA affects the long association fibers that connect multiple distant cortical areas and is, therefore, more likely to interfere with cognitive and executive functions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with prior observations in other conditions; the extent of PLA when compared with SLA more strongly correlates with cognitive decline in the nondemented elderly population, [14][15][16] progression from mild cognitive impairment to Alzheimer disease, 17 burden of aortic atherosclerosis, 18 poor functional outcome after stroke, 11 and risk of recurrent hemorrhage in patients with lobar intracerebral hemorrhage. 19 It has been suggested that SLA predominantly disrupts the short association fibers that connect adjacent gyri to each other, whereas PLA affects the long association fibers that connect multiple distant cortical areas and is, therefore, more likely to interfere with cognitive and executive functions.…”
Section: Discussionsupporting
confidence: 92%
“…Leukoaraiosis is associated with progression of cognitive impairment, gait abnormalities, poor functional outcome, increased mortality, higher risk of hemorrhage after thrombolysis, and long-term recurrence after ischemic stroke. [8][9][10][11][12][13] This study extends our knowledge on the relationship between leukoaraiosis and ischemic stroke by showing that leukoaraiosis is also a risk factor for early stroke recurrence. After controlling for initial stroke severity, conventional stroke risk factors, underlying stroke mechanism, and preventive stroke treatment, patients with extensive leukoaraiosis were 1.5× more likely to have another ischemic stroke in the short-term than those without extensive leukoaraiosis.…”
Section: Discussionmentioning
confidence: 59%
“…[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] Among the 19 studies that examined functional status at 30 or 90 days, none were designed to evaluate the quality of care at the hospital level or predict outcomes at the provider level. Each study examined functional status outcomes at the patient level, with 13 studies specifying an independent variable.…”
Section: Review Of Evidence On Models That Evaluate Predictors Of Funmentioning
confidence: 99%
“…[8][9][10] Oligodendrocytes are particularly sensitive to ischemic and oxidative stress, 7,34,35 and there is a correlation between white matter involvement and poor long-term functional outcomes after stroke. 5,6 It may be that dalfampridine is acting on demyelinated but intact pathways that are functionally impaired yet have synaptic connections in areas remote from the lesion, as Rats at the end of the dose-escalation study were larger than the rats at the end of the double cross-over study (488 vs 525 g on average, respectively). MCAO indicates middle cerebral artery occlusion.…”
Section: Strokementioning
confidence: 99%
“…2,3 Significant white matter involvement occurs in the majority of strokes 4 and has been linked to poorer long-term functional outcomes. 5,6 Additionally, oligodendrocytes have been shown to be particularly sensitive to ischemic insult. 7 The potassium channel blocker, 4-aminopyridine, known in the United States by its nonproprietary drug name dalfampridine, and in the rest of the world as fampridine, has been studied for many years for its potential to improve conduction in demyelinated axons.…”
mentioning
confidence: 99%